Effect of protocatechuic acid incorporation on the physical, mechanical, structural and antioxidant properties of chitosan film. (December 2017) - Liu, Jun; Liu, Shuang; Wu, Qingqing; Gu, Yanyang; Kan, Juan; Jin, Changhai
Abstract: Novel antioxidant active packaging films were prepared by incorporating different amount of protocatechuic acid (PA) into chitosan film. Effect of PA incorporation content on the physical, mechanical, structural and antioxidant properties of chitosan-PA composite films was investigated. As compared with chitosan film, chitosan-PA composite films exhibited higher thicknesses, water solubility and opacity, whereas lower light transmission, moisture contents, water vapor permeability and elongation at break. In addition, these properties of chitosan-PA composite films were closely related with the content of PA incorporated. The surface and cross-section of chitosan-PA composite films were more homogenous and smoother when 0.5% or 1.0% of PA was incorporated. However, big cavities and large crystals were observed in the inner of composite film with 2.0% of PA. FT-IR spectra indicated the molecular interactions between PA and chitosan were through non-covalent bonds rather than covalent linkages. Moreover, chitosan-PA composite films released much more total phenolic content and antioxidant into aqueous and fatty food simulants than chitosan film. Our results suggest chitosan-PA composite films incorporated with 0.5% or 1.0% of PA can be used as novel antioxidant food packaging materials. Graphical abstract: Highlights: Chitosan-based composite films were prepared by adding protocatechuic acid (PA). PA affected films' physical, mechanical, structural and antioxidant properties. Films incorporated with 0.5% or 1.0% of PA showed better functionality. Molecular interactions between PA and chitosan were formed through non-covalent bonds. Antioxidant could be released from films into food simulants.